(untitled) (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2024)
Batulayang Tourism Village is one of West Java Province’s sustainable tourism villages. Gender equality in environmental preservation are an important factor in efforts to preserve the ecological environment. Men and women share equal responsibility for environmental preservation. The purpose of this study is to examine the relationship between environmental preservation and the level of the gender gap. This study uses a mixed method exploratory sequential design approach, applying in-depth interviews for qualitative followed by questionnaires for quantitative data collection. The respondents in this research are 30 household members of the environmental community and 5 people research subjects who were in Ecovillage Program. The Spearman Rank Correlation and Chi-Square Test were utilised in this data processing for quantitative data. The research findings indicate that the Ecovillage Programe has sufficiently increased community participation to care more about the surrounding environment; however, in its implementation in the household sphere, the lack of gender-based environmental awareness causes there to still be a gap between husbands and wives in environmental management because environmental management is often associated with women’s domestic role.